Advanced home wiring : current with 2023-2026 electrical codes. (Cool Springs Press, an imprint of the Quarto Group, 2024)
"Take on advanced wiring projects with confidence with up-to-date advice and photo-illustrated step-by-step instructions from a trusted brand. Equipped to comply with the 2023-2026 electrical codes and chock-full of information that' hard to find online, BLACK+DECKER Advanced Home Wiring, Updated 6th Edition, gives you an in-depth look at more sophisticated products and more advanced projects in home wiring. Some of these projects include: A step-by-step demonstration of the right way to wire a three-way switch in any situation; A closer look at 'available neutral' requirements and how they impact traditional wiring configurations; Information on weatherproof boxes and conduit; A primer on three-phase power; A guide to 240-volt circuitry that eliminates all the confusion"--